A state of the art review on biomass processing and conversion technologies to produce hydrogen and its recovery via membrane separation. (29th May 2020) - Shahbaz, Muhammad; Al-Ansari, Tareq; Aslam, Muhammad; Khan, Zakir; Inayat, Abrar; Athar, Muhammad; Naqvi, Salman Raza; Ahmed, Muahammad Ajaz; McKay, Gordon
Abstract: Hydrogen is a zero-emission green fuel containing sufficient energy potentially suitable for electricity generation. Currently, large quantities of hydrogen are produced using classical fossil fuels. Nevertheless, the finite quantities of these resources have compelled the global community to look into using more sustainable and environmentally friendly resources such as bio-based waste. There are several approaches, to convert biomass to hydrogen, among which the thermochemical and biological processes are considered as the most important ones. The aim of this review paper is twofold, namely, (a) to evaluate hydrogen production and biomass processing methods to give a better insight into their potential merits and identify gaps for sustainable hydrogen generation, and (b) to evaluate current and future opportunities in membrane technology for hydrogen separation and purification from biomass processing. By fulfilling these gaps, the objectives of economical, sustainable, and environmentally-friendly resources for hydrogen production and separation can be recommended. Highlights: Thermochemical conversion technologies for hydrogen production. Gasification technologies review for hydrogen production. Biological routes for hydrogen production. Potential of membrane applications for hydrogen separation from syngas. Prospective of hydrogen as future of energy.